Effect of Liquid Organic Fertilizer from Chicken, Goat, and Cow Manure on the Content of Nitrogen, Phosphorus, Potassium, and Lead in Soil, and on Stem and Fruit Yield of Tomato - Mindari, Wanti; Widjayani, Bakti Wisnu; Sasongko, Purnomo Edi; Isnaini, Farichah; Siswanto, Siswanto (Agrotechnology Research Journal, 2024)
Using manure in the form of liquid organic fertilizer (LOF) influences the heavy metal levels absorbed by plants, which can affect both plant quality and human health. This research aims to assess the impact of LOF on soil pH, total nitrogen, available phosphorus, lead levels, and the fruit yield of tomatoes. A factorial completely randomized design (CRD) was employed, with the first factor being three types of LOF from chicken, goat, and cow manure and the second factor being three doses of LOF: 5, 10, and 15 mL. The study utilized tomato plants grown in latosol soil. Results indicated that the application of LOF from the three manure types affected soil nitrogen, soil lead, and tomato yield. The addition of LOF also influenced lead content and tomato production. However, the use of chicken manure is not recommended due to high lead accumulation in soil and plants. The optimal LOF dose was found to be 5-10 mL, which maintained lead levels within safe limits. The best tomato fruit yield was achieved with 5 mL of goat manure LOF, resulting in low metal accumulation.